Literacy development in Turkish-Arabic speaking bilingual children - İlerten, Ferda. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2021., 2021)
This study explored the role of cognitive and linguistic variables in the development of word reading and reading comprehension in Turkish-Arabic bilingual children. Ninety-two 2nd grade Turkish-Arabic simultaneous bilingual and thirty-five Turkish monolingual children participated in the study. The performance of both groups in phonological awareness (PA), phonological memory (PM), rapid automatized naming (RAN), morphosyntactic awareness (MA), morphological awareness test time (MATT), processing speed (PS) and vocabulary knowledge (VK) was examined and compared through independent samples t-test with bootstrapping function. Bilingual children outperformed monolingual children in PA and PS. The performance of both groups was similar in other tasks. The predictors of reading skills were investigated separately for both groups of participants through stepwise regression analyses. The results revealed that while MATT and RAN predicted word reading efficiency in the bilingual group, MATT and PA were the significant predictors of word reading in the Turkish monolingual group. As for reading comprehension, the groups displayed different patterns. While WRead, VK and PM were the most powerful indicators of comprehension in the Turkish-Arabic bilingual group, MA was the only significant precursor of reading comprehension in the Turkish monolingual children. These differences indicated that the reliance of the monolingual and bilingual children on linguistic and cognitive mechanisms ranged in word reading and reading comprehension.
Keywords: Bilingualism in children.; Children -- Turkey -- Languages.